THE LEVEL OF KNOWLEDGE WITH CITIZENS’ BEHAVIOR IN IMPLEMENTING HEALTH PROTOCOL IN THE NEW NORMAL TIME OF THE COVID-19 PANDEMIC IN ARA CONDONG VILLAGE, KEC. STABAT KAB. LANGKAT, YEAR 2021 - Juliati Juliati; Aisyah Aisyah (Science Midwifery, 2021)
Knowledge is the result of "knowing." It occurs after a person feels an object, primarily through the eyes and ears. Behavior is the biological manifestations of the interaction between individual and environment, from the most obvious to the invisible, from the felt to the least regarded. Health protocols are the rules and regulations that all parties need to follow to carry out activities safely during the COVID-19 pandemic. This type of research is research that describes using a cross-sectional study design. The research objective is to determine the Relationship between Knowledge Level and Citizen Behavior in Carrying Out Health Protocols in the New Normal Pandemic Covid-19 Period in Ara Condong Village, Kec. Stabat Kab. Langkat 2021. In this study, the sampling technique was carried out by taking 10% of the existing Population. So in this study, 10% of 550 is 55. So the Sample in this study amounted to 55 people. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1. The results obtained are p.value = 0.000 at df = 1 where sig <α (0.000 <0, 05) it can be seen that there is a relationship between the level of knowledge and the behavior of residents in carrying out health protocols during the New Normal Pandemic Covid-19 in Ara Condong Village, the districts of Stabat, Langkat. The results of this study are expected to the health workers in Ara Condong Village always to provide information about the implementation of health protocols so that public knowledge will improve and support good behavior